Advancing age and the risk of bleomycin pulmonary toxicity in a largely older cohort of patients with newly diagnosed Hodgkin Lymphoma. Issue 1 (January 2020) - Thomas, Theodore S.; Luo, Suhong; Reagan, Patrick M.; Keller, Jesse W.; Sanfilippo, Kristen M.; Carson, Kenneth R.
Abstract: Objectives: In patients with Hodgkin Lymphoma (HL), the relationship between increasing age and bleomycin pulmonary toxicity (BPT) remains unclear. This study explores associations between age and BPT in a real-world cohort of largely older patients with HL. Material and methods: This study retrospectively evaluated a nationwide patient cohort of United States Veterans diagnosed with HL in VA medical centers between October 1, 2002 and December 31, 2013 (follow up through April 15, 2016). The primary outcome was the development BPT, defined as: ambient air oxygen saturations <92% with pulmonary infiltrates on chest radiograph and no other etiologies OR clinician documentation of BPT. Multivariable logistic regression was used to evaluate variables associated with development of BPT. Cox proportional hazards analysis was performed to evaluate the risk of death up-to 5-years from diagnosis. Results: Overall, 847 patients received chemotherapy and 739 of these patients received bleomycin. Sixty-six patients (9.3%) developed BPT. The incidence of BPT per age category: 0.03 (9/262), 0.07 (13/188), 0.13 (23/171), and 0.24 (21/88) for age categories: ≤ 49, 50–59, 60–69 and ≥ 70 years. Odds of BPT steadily increased with advancing age (compared to patients age ≤ 49 years) with odds ratios of 1.65 (95% CI 0.68–4.03), 3.24 (1.43–7.34), 6.01(2.52–7.34) for age categories 50–59, 60–69 and ≥ 70 years, respectively. The was no association between bleomycin and risk of death up-to 5-years [HR: 0.87; 95% CI (0.61–1.23)]. Conclusion: This study demonstrates a direct relationship between age >60 years and odds of developing clinically significant BPT.